End Colostomy With or Without Mesh to Prevent a Parastomal Hernia (GRECCAR 7): A Prospective, Randomized, Double Blinded, Multicentre Trial. Issue 6 (December 2021) - Prudhomme, Michel; Rullier, Eric; Lakkis, Zaher; Cotte, Eddy; Panis, Yves; Meunier, Bernard; Rouanet, Philippe; Tuech, Jean-Jacques; Jafari, Mehrdad; Portier, Guillaume; Dubois, Anne; Sielezneff, Igor; et al.
Abstract : Objective: To evaluate whether systematic mesh implantation upon primary colostomy creation was effective to prevent PSH. Summary of Background Data: Previous randomized trials on prevention of PSH by mesh placement have shown contradictory results. Methods: This was a prospective, randomized controlled trial in 18 hospitals in France on patients aged ≥18 receiving a first colostomy for an indication other than infection. Participants were randomized by blocks of random size, stratified by center in a 1:1 ratio to colostomy with or without a synthetic, lightweight monofilament mesh. Patients and outcome assessors were blinded to patient group. The primary endpoint was clinically diagnosed PSH rate at 24 months of the intention-to-treat population. This trial was registered at ClinicalTrials.gov, number NCT01380860. Results: From November 2012 to October 2016, 200 patients were enrolled. Finally, 65 patients remained in the no mesh group (Group A) and 70 in the mesh group (Group B) at 24 months with the most common reason for drop-out being death (n = 41). At 24 months, PSH was clinically detected in 28 patients (28%) in Group A and 30 (31%) in Group B [ P = 0.77, odds ratio = 1.15 95% confidence interval = (0.62;2.13)]. Stoma-related complications were reported in 32 Group A patients and 37 Group B patients, but no mesh infections. There were no deaths related to mesh insertion. Conclusion: We failed to show efficiency of a prophylactic mesh on PSH rate. Placement of a mesh in a retro-muscular position with a central incision to allow colon passage cannot be recommended to prevent PSH. Optimization of mesh location and reinforcement material should be performed. Abstract : Supplemental Digital Content is available in the text